ARCHITECTONICS OF MEMORY IN THE PROSE OF S. AFLATUNI: CONSTRUCTION OF PLACES OF MEMORY AND CULTURAL REMINISCENCES (Educator Insights: Journal of Teaching Theory and Practice, 2025)
The article explores the architecture of memory in S. Aflatuni’s prose. The aim is to identify memory structures through imagery, space, and symbols. The study applies theories by Nora, Assmann, and Ricoeur. Novelty lies in the interdisciplinary approach.